PENGARUH PENDAPATAN ASLI DAERAH, UPAH MINIMUM REGIONAL, DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT PENGANGGURAN DI KAWASAN NON-SARBAGITA PROVINSI BALI - Yeimo, Jeremi Erick Fandy; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.11.TAHUN.2022, 2022)
The purpose of this study was to analyze the effect of original local government revenue  (PAD) , regional minimum wage  (UMR) , and economic growth simultaneously and partially on the unemployment rate in Non-Sarbagita Regions in Bali Province. The research method used in this research is observation with data collection through a literature study. The data used in this study is secondary data obtained from BPS Bali Province related to original local government revenue, regional minimum wage, economic growth, and unemployment rate. This study uses panel data, which is a combination of time-series data (2014-2020) and cross-section data (5 districts/cities in Bali Province) so that the total observations are 35 observations. The analysis technique used is multiple linear regression. Based on the results of the analysis, it was found that the variables of original local government revenue, regional minimum wages, and economic growth had a significant effect on the unemployment rate in the Non-Sarbagita area, Bali Province. Partially, the original local government revenue variable has a positive and significant effect on the unemployment rate in the Non-Sarbagita Region, Bali Province, while the regional minimum wage and economic growth have a negative and significant impact on the unemployment rate in the Non-Sarbagita Region, Bali Province